2017
DOI: 10.1186/s12974-017-0843-4
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 deficiency alters macrophage phenotype through an IL-10/STAT3 dependent mechanism: implications for traumatic brain injury

Abstract: BackgroundNADPH oxidase (NOX2) is an enzyme system that generates reactive oxygen species (ROS) in microglia and macrophages. Excessive ROS production is linked with neuroinflammation and chronic neurodegeneration following traumatic brain injury (TBI). Redox signaling regulates macrophage/microglial phenotypic responses (pro-inflammatory versus anti-inflammatory), and NOX2 inhibition following moderate-to-severe TBI markedly reduces pro-inflammatory activation of macrophages/microglia resulting in concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 63 publications
3
53
0
Order By: Relevance
“…STAT3 plays a critical role in macrophage polarization . In order to elucidate the mechanism underlying melatonin's regulation on microglia polarization, we examined the protein levels of STAT3 and p‐STAT3 in BV2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 plays a critical role in macrophage polarization . In order to elucidate the mechanism underlying melatonin's regulation on microglia polarization, we examined the protein levels of STAT3 and p‐STAT3 in BV2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Microglia/macrophage polarization is modulated by many transcription factors, such as STATs and PPAR‐γ STAT3 was demonstrated to play a dominant role in IL‐10‐mediated anti‐inflammatory effects in human macrophages . In addition, STAT3 appeared to be critical in regulating macrophage/microglia polarization to anti‐inflammatory phenotype in the TBI brain . Besides, resveratrol was reported to suppress the LPS‐induced pro‐inflammatory response in microglia cells through the activation of STAT3 pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding quantification of immunofluorescence and in situ mRNA hybridization has been provided by (Allen et al, 2016; Barrett et al, 2017; Villapol et al, 2017). Briefly:

Positive in situ mRNA hybridization signal consists of a punctate signal representing a single mRNA transcript (Wang et al, 2012).

…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that a mixed pattern of both pro-inflammatory and anti-inflammatory cytokine expression occurred in microglia/macrophages in the first week after TBI. Also, we have previously shown that IL-10 levels are significantly increased in microglia/macrophages in the injured cortex of NOX2 −/− mice (Barrett et al, 2017). …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation